Anhedonia: Current and future treatments - Alessandro Serretti (PCN Reports)
Abstract Anhedonia is a transdiagnostic domain that leads to poor disorder outcome and low remission rates. This narrative review describes a broad range of interventions targeting anhedonia, including pharmacological, neuromodulatory, behavioral, and lifestyle‐based approaches. Drugs such as vortioxetine, agomelatine, bupropion, ketamine, and brexpiprazole show promising anti‐anhedonic effects, while traditional antidepressants, such as serotonin‐norepinephrine reuptake inhibitors (SNRIs) and, even more so, selective serotonin reuptake inhibitors (SSRIs), are less effective. Neuromodulation techniques, including repetitive transcranial magnetic stimulation, transcranial direct current stimulation, and transcutaneous auricular vagus nerve stimulation, proved effective at improving anhedonia, particularly when used in targeted areas. Psychotherapeutic interventions, including behavioral activation, mindfulness‐based strategies, and savoring techniques, also help re‐engage patients with pleasurable activities and enhance positive affect. Innovative treatments, such as aticaprant and psilocybin, showed promising results. Substantial evidence suggests that improving anhedonia leads to better psychosocial functioning, quality of life, and sustained remission. Although most data come from short‐term studies, several long‐term analyses suggest that maintaining hedonic improvements is feasible and beneficial. The reviewed evidence underscores the importance of routine assessment of anhedonia and the integration of symptom‐specific strategies. Tailoring interventions to address individual patterns of reward disruption may optimize outcomes for patients with anhedonia.